Genomics and Transcriptomics Analyses of the Oil-Accumulating Basidiomycete Yeast Trichosporon oleaginosus: Insights into Substrate Utilization and Alternative Evolutionary Trajectories of Fungal Mating Systems - Robert Kourist (American Society for Microbiology, 2015)
ABSTRACT Microbial fermentation of agro-industrial waste holds great potential for reducing the environmental impact associated with the production of lipids for industrial purposes from plant biomass. However, the chemical complexity of many residues currently prevents efficient conversion into lipids, creating a high demand for strains with the ability to utilize all energy-rich components of agricultural residues. Here, we present results of genome and transcriptome analyses of Trichosporon oleaginosus. This oil-accumulating yeast is able to grow on a wide variety of substrates, including pentoses and N-acetylglucosamine, making it an interesting candidate for biotechnological applications. Transcriptomics shows specific changes in gene expression patterns under lipid-accumulating conditions. Furthermore, gene content and expression analyses indicate that T. oleaginosus is well-adapted for the utilization of chitin-rich biomass. We also focused on the T. oleaginosus mating type, because this species is a member of the Tremellomycetes, a group that has been intensively analyzed as a model for the evolution of sexual development, the best-studied member being Cryptococcus neoformans. The structure of the T. oleaginosus mating-type regions differs significantly from that of other Tremellomycetes and reveals a new evolutionary trajectory paradigm. Comparative analysis shows that recruitment of developmental genes to the ancestral tetrapolar mating-type loci occurred independently in the Trichosporon and Cryptococcus lineages, supporting the hypothesis of a trend toward larger mating-type regions in fungi. IMPORTANCE Finite fossil fuel resources pose sustainability challenges to society and industry. Microbial oils are a sustainable feedstock for biofuel and chemical production that does not compete with food production. We describe genome and transcriptome analyses of the oleaginous yeast Trichosporon oleaginosus, which can accumulate up to 70% of its dry weight as lipids. In contrast to conventional yeasts, this organism not only shows an absence of diauxic effect while fermenting hexoses and pentoses but also effectively utilizes xylose and N-acetylglucosamine, which are building blocks of lignocellulose and chitin, respectively. Transcriptome analysis revealed metabolic networks that govern conversion of xylose or N-acetylglucosamine as well as lipid accumulation. These data form the basis for a targeted strain optimization strategy. Furthermore, analysis of the mating type of T. oleaginosus supports the hypothesis of a trend toward larger mating-type regions in fungi, similar to the evolution of sex chromosomes in animals and plants.